Electrolytic In-Process Dressing (ELID) grinding for nano-surface generation - Saleh, Tanveer; Rahman, Mustafizur (Elsevier, 2014)
Electrolytic In-Process Dressing (ELID) grinding using a super-abrasive wheel has opened up the gateway for ductile machining of hard and brittle materials to achieve nanometric surface finish. ELID grinding uses anodic dissolution of a metal-bonded grinding wheel to ensure constant protrusion of the sharp grits to realize smooth and stable grinding operation throughout. A pulsed DC power supply is used in this purpose and the metal-bonded wheel is connected to the positive terminal, whereas the electrode (copper/brass) is connected to the negative terminal of the power supply. This chapter introduces ELID grinding to the readers. Comprehensive discussions on various aspects of ELID grinding are also covered.